The impacts of IFPRI's Global Research Program on the Sustainable Development of Less-Favored Areas - International Food Policy Research Institute (International Food Policy Research Institute, 2008)
IFPRI's Global Research Program on the Sustainable Development of Less-Favored Areas was initiated in 1998, with the goals of (1) providing empirical evidence on appropriate development strategies and public investments for improving the well-being of individuals living in less-favored areas (LFAs); and (2) assessing the appropriate targeting of various public investments to favored versus less-favored areas. The program's research activities generally were confined to addressing the first of these objectives.